TREATMENT OF DIABETIC PATIENTS—Observations on the Use of Carbutamide and Tolbutamide - Splitter, Stanford (1956)
Of a group of 32 patients with diabetes, 26 had a favorable modification of the disease in response to administration of butyl-sulfonyl-urea. All but one of the patients who had good response were past the age of 38. All diabetic patients included in this group were those with little or no tendency to ketosis after cessation of insulin administration. No toxic manifestations were noted except for a slight decrease in leukocytes in one case.